2020
DOI: 10.1344/jesb2020.1.j073
|View full text |Cite
|
Sign up to set email alerts
|

Standing the test of time: External factors influencing family firm longevity in Germany and Spain during the twentieth century

Abstract: While most research on family business longevity focuses on how internal corporate governance issue impact resilience, the aim of this article is to foreground the relevance of external environmental factors, and to do so in an internationally comparative perspective. By historically comparing the largest family businesses in Germany and Spain in the twentieth century, we find that they differ significantly in age and ask how external factors help us better understand these variances. After analysing the insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Other studies have sought to assess, often rather deterministically, how external factors influence the longevity of family businesses (Riviezzo et al, 2015). Different environmental aspects such as governmental institutions (Fernández-Moya et al, 2020), legal frameworks (Carney et al, 2014), and networks (Ciravegna et al, 2020) have been found to greatly influence longevity. Little attention has, however, been paid to the interface between family businesses and the context in which they operate, thereby overlooking the role potentially played by the ongoing engagement of family businesses with their external stakeholders (Le Breton -Miller & Miller, 2015).…”
Section: Family Business and Longevitymentioning
confidence: 99%
“…Other studies have sought to assess, often rather deterministically, how external factors influence the longevity of family businesses (Riviezzo et al, 2015). Different environmental aspects such as governmental institutions (Fernández-Moya et al, 2020), legal frameworks (Carney et al, 2014), and networks (Ciravegna et al, 2020) have been found to greatly influence longevity. Little attention has, however, been paid to the interface between family businesses and the context in which they operate, thereby overlooking the role potentially played by the ongoing engagement of family businesses with their external stakeholders (Le Breton -Miller & Miller, 2015).…”
Section: Family Business and Longevitymentioning
confidence: 99%